Creation of Clusters of Small Enterprises of the Region - Kiseleva, Natalia V.; Panichkina, Marina V.; Klochko, Elena N.; Nikonorova, Alla V.; Kireev, Sergey V. (International Journal of Economics and Financial Issues, 2016)
Under the conditions of continuous economic progress, modernization of production, development of the world market there is the need for increasing competitiveness of small enterprises of the country and regions. This dynamics of changes demands new approaches to socio-economic development of the Russian industries. Each region of the country can be competitive not only in the domestic market, but also and in the world if it uses the reserve which has necessary economic, intellectual and financial potential. Thus, one of the ways of the effective realization of economic potential and stimulation of economic growth is the creation of competitive regional clusters, both large-scale organizations and small enterprises. Now the given problem is one of essential for the decision in the sphere of economic regional government as the analysis of world practice shows rather high efficiency of development of economies of many countries on the basis of use of cluster approach as opposed to branch that is acceptable for our country. The government of Russia also defined cluster approach as the main instrument of management of regional development. However, this approach demands detailed studying, first of all, from the point of view of adaptation of the international experience to the Russian conditions. Keywords: cluster, small enterprises, development, region, economic progress JEL Classifications: A10, C38, O18